Pelatihan Pemberdayaan Kantin Sekolah BERHAZI (Beragam, Halal, Bergizi) di Sekolah Menengah Pertama Kota Parepare - Andi Selvi Yusnitasari; Wahiduddin Wahiduddin; Ryza Jazid Burhanuddin Nur; Marini Amalia (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
The school canteen is one of the important school facilities in supporting the teaching and learning process. However, a number of schools in Indonesia do not have canteens and a number of other schools have canteens of substandard quality. In order to grow and develop optimally, students must consume food that is safe, healthy, halal and nutritious. Therefore, schools play a role in providing quality food and drinks for students in their environment. Parepare City as a child-friendly city with the nindya category, the local government has the responsibility to fulfill children's rights and protect, one of which is the fulfillment of school children's snack food according to nutritional, halal and clean standards. The activities carried out are conducting training to the school's academic community, which includes food handlers and teachers. The training material provided covers the concept of the BERHAZI canteen (diverse, halal and nutritious), balanced nutrition and indicators of the BERHAZI canteen. Participants who take part in the training become working group teams (Pokja) for the management of BERHAZI canteens in their respective schools. Schools are expected to apply the BERHAZI canteen concept in their respective schools so that they can become a pilot canteen in Parepare City.